The impact of training in a pupil centred behaviour plan on staff self-efficacy, staff burnout, and pupil challenging behaviour - Cooke, Heather (2014)
Challenging behaviour in schools is a phenomenon focused on by a number of educational documents (Ofsted, 2010) and the media (Vasager, 2011). Challenging behaviour has been shown to have negative impact on a number of student and staff outcomes (DfE, 2012a). Staff outcomes impacted by challenging behaviour include increasing burnout (Crone, Hawken & Bergstrom, 2007) and decreasing self-efficacy (Mitchell & Hastings, 2001), which have been connected to negative impact on staff health (Hastings & Bham, 2003). Time allocated to staff training in schools is decreasing (Bubb & Earley, 2013), highlighting a need for research which considers how school staff can be supported in the limited time available.